Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-180
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Range, Dynamism and Level in Postcolonial Varieties of English: A Comparison of Educated Indian English and British English

Abstract: Pitch range (difference between maximum and minimum pitch), pitch dynamism and mean pitch level have been shown to differ between varieties of English, and such differences can lead to (un)favourable judgements about a speaker's attitude and likeability. Little is known about pitch range in nativised varieties of English, which are spoken in postcolonial countries. While in many functional and structural ways they are similar to native varieties, in other ways they resemble learner varieties. Since learners co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Though small differences in mean f0 between read and spontaneous speech have been reported, read speech has been found to be an overall reliable medium for studies of f0 patterns [31]. Recent research has, however, shown some differences between the two speech styles for speakers of IndE [23]. We consider the implications of these findings further, in relation to both IndE and to Indian L1s, in our discussion.…”
Section: Materials and Processingmentioning
confidence: 88%
See 4 more Smart Citations
“…Though small differences in mean f0 between read and spontaneous speech have been reported, read speech has been found to be an overall reliable medium for studies of f0 patterns [31]. Recent research has, however, shown some differences between the two speech styles for speakers of IndE [23]. We consider the implications of these findings further, in relation to both IndE and to Indian L1s, in our discussion.…”
Section: Materials and Processingmentioning
confidence: 88%
“…These include standard deviation (SD) and maximum minus minimum f0 (max-min f0). We also added a measure of pitch dynamism quotient (pdq), which was calculated by dividing the SD in f0 by its mean in Hz [23,37]. The latter allows us to compare findings with those of [23].…”
Section: Measurements and Analysismentioning
confidence: 99%
See 3 more Smart Citations